A systematic review of the effects of Equol (Soy Metabolite) on breast cancer - Hod, Rafidah; Maniam, Sandra; Mohd Nor, Nurul Huda (Multidisciplinary Digital Publishing Institute, 2021)
Equol is a soy isoflavone metabolite that can be produced by intestinal bacteria. It is lipophilic and resembles natural oestrogens with an affinity to oestrogen receptors. This review is focused on how equol affects breast cancer, as evidenced by in vivo and in vitro studies. Equol is considered chemoprotective in specific endocrine-related pathologies, such as breast cancer, prostate cancer, cardiovascular diseases, and menopausal symptoms. In humans, not everyone can produce equol from gut metabolism. It is postulated that equol producers benefit more than non-equol producers for all the endocrine-related effects. Equol exists in two enantiomers of R-equol and S-equol. Earlier studies, however, did not specify which enantiomer was being used. This review considers equol’s type and concentration variations, pathways affected, and its outcome in in vivo and in vitro studies.